Beyond health care providers' recommendations: understanding influences on infant feeding choices of women with HIV in the Eastern Cape, South Africa - Oladele Vincent Adeniyi; Anthony Idowu Ajayi; Moshood Issah; Eyitayo Omolara Owolabi; Daniel Ter Goon; Gordana Avramovic; John Lambert (BMC, 2019)
Abstract Background Despite the array of studies on infant feeding practices of HIV-infected women, gaps still exist in the understanding of the underlying reasons for their infant feeding choices. Potential for behavioural change exists, especially in the light of the 2016 updated World Health Organization guideline on HIV and infant feeding. The aim of this paper is to determine the rate of adoption of exclusive breastfeeding in this cohort, examine the determinants of infant feeding choices of HIV-infected women and assess the underlying reasons for these choices. Methods This was a mixed methods study conducted between September 2015 and May 2016. It analyses the quantitative and qualitative data of 1662 peripartum women enrolled in the East London Prospective Cohort Study across three large maternity services in the Eastern Cape. Women with HIV reported their preferred choices of infant feeding. In addition, participants explained the underlying reasons for their choices. Descriptive and inferential statistics summarised the quantitative data, while thematic content analysis was performed on qualitative data. Results Of the 1662 women with complete responses, 80.3% opted to exclusively breastfeed their babies. In the adjusted model, up to grade 12 education level (AOR: 1.81; 95% CI: 1.14, 2.86), rural/peri-urban residence (AOR:1.44; 95% CI: 1.05, 1.96), alcohol use (AOR: 1.65; 95% CI: 1.25, 2.18), negative or unknown HIV status at booking (AOR:1.85; 95% CI:1.27, 2.70), currently married (AOR:1.43; 95% CI:1.01, 2.02) and WHO Clinical Stage 2-4 (AOR:1.77; 95% CI: 1.15, 2.72) were significantly associated with the decision to exclusively breastfeed. Health care providers' recommendations, perceived benefits of breastfeeding, unaffordability of formula feeding, and coercion were the underlying reasons for wanting to breastfeed; while work/school-related demands, breast-related issues, and fear of infecting the baby influenced their decision to formula feed. Conclusion The majority of HIV-infected women chose to breastfeed their babies in the Eastern Cape. Following up on these women to ensure they breastfeed exclusively, while also addressing their possible concerns, could be an important policy intervention. Future studies should focus on how early infant feeding decisions change over time, as well as the health outcomes for mother and child.